Harga dan Promosi terhadap Keputusan Pembelian Online Shopeefood - Teti Safari; Hesti Ristanto; Dwi Astutik (STIE Widya Manggala, 2023)
This study aims to determine the partial and simultaneous influence of price and promotion on purchasing decisions at online (Shopee Food, Grab Foods) for STIE “YKP” Yogyakarta Semarang students. This research method uses quantitative methods. The population in this study is the total number of students of STIE “YKP” Yogyakarta, with a sample of 100 students. The data collection technique used an online questionnaire. The data analysis technique used multiple linear regression analysis. The results show that the price, promotion has a significant effect on purchasing decisions at ShopeeFood.